Nodal histiocytic sarcoma with prominent eosinophilic infiltration: expression of eotaxin-2 on tumor cells - Rintaro Ohe; Takanobu Kabasawa; Aya Utsunomiya; Yuka Urano; Takumi Kitaoka; Kazushi Suzuki; Naing Ye Aung; Ichiro Kawamura; Katsushi Tajima; Tomoharu Ishiyama; Mitsunori Yamakawa (BMC, 2021)
Abstract Background Histiocytic sarcoma (HS) is a rare neoplasm showing morphological and immunophenotypic features of mature tissue histiocytes. We report a patient with nodal HS exhibiting prominent reactive eosinophilic infiltration. Case presentation A 68-year-old man presented with intermittent left lower abdominal pain and weight loss over 3 months. A computed tomography scan revealed multiple abdominal nodules. Open biopsy of the mesenteric tumors was performed for definitive diagnosis. Histologically, the tumor was comprised of a diffuse noncohesive proliferation of pleomorphic large cells, including multinucleated cells. Neoplastic cells were positive for histiocytic markers (CD68, CD163, and LIGHT) and PD-L1 but lacked markers of Langerhans cells, follicular dendritic cells, and epithelial cells. Frequent reactive inflammatory cells were intermingled in the background. Interestingly, prominent eosinophilic infiltration was also noted. Spindle neoplastic cells were prone to be present around areas with little to no eosinophilic infiltration and exhibiting fibrosis and lymphatic vessel proliferation. Conversely, polygonal neoplastic cells were prone to be present around areas with relatively large amounts of eosinophilic infiltration without fibrosis or lymphatic vessel proliferation. Immunohistochemically, the tumor cells and reactive eosinophils expressed eotaxin-2 and eotaxin-3, respectively. Conclusion We revealed that eotaxins induced the selective migration of eosinophils into tissues in this case. These eosinophils may affect the tumor remodeling and tumor biology characteristics of HS, such as fibrosis and lymphatic vessel proliferation.